The evolution and appearance of C3 duplications in fish originate an exclusive teleost c3 gene form with anti-inflammatory activity. - Gabriel Forn-Cuní; Edimara S Reis; Sonia Dios; David Posada; John D Lambris; Antonio Figueras; Beatriz Novoa (PLoS ONE)
The complement system acts as a first line of defense and promotes organism homeostasis by modulating the fates of diverse physiological processes. Multiple copies of component genes have been previously identified in fish, suggesting a key role for this system in aquatic organisms. Herein, we confirm the presence of three different previously reported complement c3 genes (c3.1, c3.2, c3.3) and identify five additional c3 genes (c3.4, c3.5, c3.6, c3.7, c3.8) in the zebrafish genome. Additionally, we evaluate the mRNA expression levels of the different c3 genes during ontogeny and in different tissues under steady-state and inflammatory conditions. Furthermore, while reconciling the phylogenetic tree with the fish species tree, we uncovered an event of c3 duplication common to all teleost fishes that gave rise to an exclusive c3 paralog (c3.7 and c3.8). These paralogs showed a distinct ability to regulate neutrophil migration in response to injury compared with the other c3 genes and may play a role in maintaining the balance between inflammatory and homeostatic processes in zebrafish.